Infiltration of Autologous Growth Factors in Chronic Tendinopathies. (15th June 2015) - Crescibene, Antonio; Napolitano, Marcello; Sbano, Raffaella; Costabile, Enrico; Almolla, Hesham
Abstract : Achilles tendinopathy and patellar tendinopathy are among the most frequent diagnoses in sports medicine. Therapeutic treatment of the disease is difficult, particularly in chronic cases. In literature, several studies suggest the employment of Platelet-Rich Plasma as a therapeutic alternative in tendinopathies. The choice of employing this method is based on the activity of growth factors contained in platelets which activate, amplify, and optimize the healing process. We selected 14 patients affected by Achilles tendinopathy and 7 patients affected by patellar tendinopathy, with a two-year final follow-up. These patients underwent a cycle of three tendinous infiltrations, after clinical and instrumental evaluation carried out by means of specific questionnaires and repeated ultrasound scans. Ultrasound scans of 18 patients showed signs of reduction in insertional irregularities. The result is confirmed by complete functional recovery of the patients, with painful symptomatology disappearing. The patients showed a clear pain reduction, along with an enhanced VISA score after the 24-month follow-up, equal to 84.2 points on a scale of 0 to 100. In conclusion, the present study provides evidence to suggest that PRP infiltration is a valid option to patients with chronic tendinopathy who did not benefit from other treatments.